POLA KOMUNIKASI ANTARPRIBADI PEKERJA SEKS KOMERSIAL (PSK) DENGAN CALON PENGGUNA JASA DI KAWASAN BUNG TOMO DENPASAR - Surya Ascaya, Gede Andre; Sugiarica Joni, I Dewa Ayu; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium, 2017)
Communication is an essential thing in every situation and condition. A good communication is also needed in prostitution business. Bali is one of the most tourist destination in the world, that makes Bali’s economical growth is good enough. In another words many places in Bali is also become a place for prostitution practice. One of them is in Bung Tomo area, Desa Pemecutan Kaja, Denpasar Utara. A prostitution practice was held in Banjar Kusuma Jati, Bung Tomo the prostitution place would be camouflage as a coffee shop, or a food stall, and that’s all is different with another prostitution places. Behind the sex transaction, there were some interesting things like the technical that was used by the prostitutes to hire the costumers, they used the verbal and also non-verbal codes. In one food stall there were some sellers who would receive some codes from the costumers. Another special thing from this prostitution practice was the communication pattern which was used by the prostitutes to get their costumer. They used some codes were aimed to make the lobbying and negotiation between the prostitutes and the costumer will be not vulgar. Key Words: Communication pattern, codes, prostitutes, prostitution.